If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-8(2-x)-5x+10=-5x+1/3(45x+3)
We move all terms to the left:
-8(2-x)-5x+10-(-5x+1/3(45x+3))=0
Domain of the equation: 3(45x+3))!=0We add all the numbers together, and all the variables
x∈R
-8(-1x+2)-5x-(-5x+1/3(45x+3))+10=0
We add all the numbers together, and all the variables
-5x-8(-1x+2)-(-5x+1/3(45x+3))+10=0
We multiply parentheses
-5x+8x-(-5x+1/3(45x+3))-16+10=0
We multiply all the terms by the denominator
-5x*3(45x+3))+8x*3(45x+3))-(-5x+1-16*3(45x+3))+10*3(45x+3))=0
Wy multiply elements
-45x^3(4+3))-(-5x-16*3(45x+3))+10*3(45x+1+3))=0
We do not support expression: x^3(4
| 2(f+1)+5=19 | | 4v+12=88 | | 7/6c+4=-10 | | 2x-7+6=x+7 | | y-1/3=1/9 | | 7h−6h=7 | | −8x+5=37 | | f(5)=10(5)+8 | | 25=3u-11 | | 3(v+8)=-9v+48 | | 2c+2c=16 | | 2.1x-5.2=13.7 | | -3+24n-48n=23+2n | | 52=-4-7b | | 10+1/3x=14 | | Y=45x+270 | | 6x-3=5-5x | | 7x+3=83 | | Y=23-1x | | 1/10+24.7=-2x | | 2(x+1)−4x=x−4 | | 6x+4=x-12 | | 5x5=4x+4 | | -3n+1/2(14n-10)=4(n+1)-9 | | −*(1+7x)−6*(−7−x)=36 | | -x+4x40/7=3 | | 6=3(p-7) | | 4(3x+7)=-35+51 | | C+8+c-4=-4(c-3)+5(c-1) | | F(x)=0.5x+1 | | -38=-17m+13 | | |3d-5|=17 |